Maysel's formula in the generalized linear micropolar thermoviscoelasticity - El-Karamany, Ahmed S. (Archives of Mechanics, 2004)
Generalizations of Maysel's formula to generalized linear micropolar thermoviscoelasticity is given. Fundamental solutions in the Laplace transform domain are obtained. The results are applicable to the following generalized thermoelasticity theories: Lord-Shulman theory with one relaxation time, Green-Lindsay theory with two relaxation times, Green-Naghdi theory of type III, and the Chandrasekharaiah and Tzou theory with dual-phase lag, as well as to the dynamic coupled theory. The cases of generalized linear micropolar thermoviscoelasticity of the Kelvin-Voigt model, and the generalized linear micropolar thermoelasticity can be obtained from the given results.